Construction of an efficient polystyrene-degrading microbial consortium based on degrading and non-degrading bacteria predominant in biofilms of marine plastic debris - Wang, Jiannan; Liu, Renju; Zhao, Sufang; Zhang, Benjuan; Shao, Zongze (Frontiers in Marine Science, 2025)
Expanded polystyrene (EPS) has caused significant pollution in marine environments, with potential EPS-degrading bacteria identified on long-term floating EPS biofilms. However, studies on bacterial interactions and consortium reconstruction based on in-situ bacterial diversity remain limited. Marine EPS wastes of different sizes were collected from subtropical coast of Xiamen island, and subjected to bacterial diversity analyses. Co-occurrence network and bacterial characterization revealed that Rhodobacterales and Rhizobiales play important roles in polystyrene (PS) degradation. Bacterial isolation characterization confirmed that Fulvimarina pelagi, Pseudosulfitobacter pseudonitzschiae, Devosia nitrariae, Cytobacillus kochii, and Cytobacillus oceanisediminis as novel PS-degraders. Based on their abundance in situ and PS degradation activity, a consortium was constructed, constituted of F. pelagi, P. halotolerans. and O. granulosus, showed a high degradation capability with PS weight loss by 18.9% in 45 days. These results contribute to marine plastic pollution remediation and resources recycling.